Bibliometric Analysis of Tourism Development Based on Disaster Mitigation Through the Scopus Database - Z. Karim, Taufik; Siregar, Hermanto; Mulatsih, Sri; Tjahjono, Boedi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
The development of the world tourism industry in daily life still focuses on the beauty of tourist attractions and the economic income of a country. Still, it ignores crisis conditions, such as disasters in tourist areas. Therefore, disaster mitigation is expected to educate the public and tourists to prepare them for a disaster. The research objective is to universally analyze the development of tourism research topics based on disaster mitigation. The research method used was bibliometric analysis. Bibliometric analysis helps identify the distribution of articles published in Scopus-indexed journals, authors, institutions, citations, countries, topic trends, keywords, and networks between authors. The research results show that the disaster mitigation process refers to structural and nonstructural mitigation actions, such as infrastructure development, increasing public knowledge about disaster mitigation, creating disaster evacuation routes, and strengthening regulations. Meanwhile, the results of the bibliometric analysis show that the country that produces the most scientific writing on tourism and disaster mitigation is Indonesia, with 49 articles, followed by China with 16 articles, the United States with 12 articles, Japan with 5 articles, India and the UK with 4 articles. These results indicate that Indonesian writers have contributed globally to tourism and disaster mitigation.